Realization Of The Learning Modalities In The Differentiated Learning For Teaching Exposition Text - Muttaqin, Muhamad Zayyinul (Universitas PGRI Semarang, 2024)
This research explores a learning experience for pupils which can be considerably improved by focusing on several learning modes when teaching English as well as investigates teacher who engages the pupils and aid their understanding of English language subjects by accommodating different learning styles. This study focuses on qualitative design with a case study where the data was achieved through both classroom observation and interview. The participants were 36 entities of students and 1 English teacher who facilitated the learning at X-1 grade in SMA Negeri 14 Semarang in academic year 2022/2023. The findings show that the realization of guided learning through learning modalities could shape differentiated learning styles where the students can possess their profile or ability to accomplish the assignment. The conclusion sets out that teachers could possibly be aware of the learners'' situation in learning certain subjects by realizing the modalities of learning modes within guided learning to teach English text (exposition text), and the field of differentiated learning style can be implemented.